Novel Utilization of Waste Marine Sponge (Demospongiae) as a Catalyst In Ultrasound-Assisted Transesterification of Waste Cooking Oil - Noor, Hindryawati; Gaanty Pragas, Maniam (Elsevier Ltd, 2015)
This study demonstrates the potential of Na-silica waste sponge as a source of low cost catalyst in the transesterification of waste cooking oil aided by ultrasound. In this work an environmentally friendly and efficient transesterification process using Na-loaded SiO2 from waste sponge skeletons as a solid catalyst is presented. The results showed that the methyl esters content of 98.4 ± 0.4 wt.% was obtainable in less than an hour (h) of reaction time at 55 °C. Optimization of reaction parameters revealed that MeOH:oil, 9:1; catalyst, 3 wt.% and reaction duration of 30 min as optimum reaction conditions. The catalyst is able to tolerant free fatty acid and moisture content up to 6% and 8%, respectively. In addition, the catalyst can be reused for seven cycles while maintaining the methyl esters content at 86.3%. Ultrasound undoubtedly assisted in achieving this remarkable result in less than 1 h reaction time. For the kinetics study at 50–60 °C, a pseudo first order model was proposed, and the activation energy of the reaction is determined as 33.45 kJ/mol using Arrhenius equation.